Efficiency, risk, and profitability of rainfed rice farming in South Sulawesi, Indonesia - Fattah, Muhammad Arifin; Arifin, Arifin; Mardiyati, Sri; Natsir, Mohammad; Muslimin, Muslimin (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2023)
Rice farming is a business that has many risks, and production risks cause fluctuations in production. Productivity influences farming income and profitability. An increase and decrease in production will affect revenue or profitability. The purpose of this study is to analyze the technical efficiency, production risk, and profitability of rainfed lowland rice farming. This research was conducted in two regencies in South Sulawesi Province, namely Maros Regency and Pangkajene Islands Regency. The sample of this study was 100 farmers in rainfed rice fields. This research used quantitative methods with a survey approach. Data were collected using observation, recording, and interview instruments, and were then analyzed using quantitative description coupled with a t-test for independent samples. The results showed that rainfed lowland rice farming in Maros Regency and Pangkajene and Archipelago Regency was technically efficient. Rainfed lowland rice farming in Maros Regency and Pangkajene Regency and Islands is at risk. Â Rainfed lowland rice farming in Maros Regency and Pangkajene Regency and the islands using profitability analysis generates income and profit, and is feasible to cultivate. Farmers need to use production inputs as recommended to increase production reduce production risk and efficiently use inputs.JEL ClassificationÂ D10; Q00; Q12